Palate and Place: Food, Third Spaces, and Identity Among First- and Second-Generation Koreans in Montgomery County, Maryland - Kim, Madeline. (Tufts University. Tisch Library., 2024)
Thesis (M.A.)--Tufts University, 2024.; Submitted to the Dept. of Urban and Environmental Policy and Planning.; Advisor: Kristin Skrabut.; Committee: Julian Agyeman.; Keywords: Urban planning, Social research, and Ethnic studies.